PENGEMBANGAN MODEL LATIHAN TEKNIK SMASH DALAM OLAHRAGA BOLA VOLI - Widha Srianto (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2018)
Abstract: This research aims to develop an training model of smash technique in the volley ball sport. The developed model is proposed to become the trainerâ€™s guidance in conducting the training of smash technique for volleyball sport. The study is elaborated by using nine steps by adapting the research stages of Borg & Gall explained as follows:Â  (1) Research and information collection, (2) Planning, (3) Develop preliminary form of product, (4) Develop preliminary form of product, (5) Main product revision, (6) Main filed testing, (7) Operasional product revision, (8) Operational field testing, and (9) Final product revision. Product trial is performed at Student Activity Units (UKM) of volley ball in Universitas Tunas Pembangunan Surakarta. usage trial is done at the volleyball club of Dhaksinarga Gunung Kidul. Instrument of data collection applied is elaborated as follows: interview guidance, observation guidance, training model effectiveness. The implemented data analysis methods include quantitative descriptive analysis and qualitative descriptive analysis. The result of research is the form of 6 training model of smash technique in the volleyball sport. From the data analysis of the expert judgement ratings, it can be conclude that the model of smash technique in the volley ball sport is rated as good and effective, so it is feasible to be used.Â